2016
DOI: 10.1016/j.jval.2016.08.395
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Screening for and Managing Identified Hypertension for Cardiovascular Disease Prevention in Vietnam

Abstract: ObjectiveTo inform development of guidelines for hypertension management in Vietnam, we evaluated the cost-effectiveness of different strategies on screening for hypertension in preventing cardiovascular disease (CVD). MethodsA decision tree was combined with a Markov model to measure incremental cost-effectiveness of different approaches to hypertension screening. Values used as input parameters for the model were taken from different sources. Various screening intervals (one-off, annually, biannually) and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 17 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…There is no enough evidence to recommend screening asymptomatic adults with no risk factor for hypertension. All studies form developed and developing countries revealed that screening adults aged 40 years with one or more risk factor is cost-effective (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). This is in line with WHO PEN package interventions for primary health care in developing countries (34).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…There is no enough evidence to recommend screening asymptomatic adults with no risk factor for hypertension. All studies form developed and developing countries revealed that screening adults aged 40 years with one or more risk factor is cost-effective (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). This is in line with WHO PEN package interventions for primary health care in developing countries (34).…”
Section: Discussionmentioning
confidence: 74%
“…Concerning the target populations four studies included people aged 40 years and above (13)(14)(15)(16), three studies included people aged 50 years and above (17)(18)(19), two studies included age 30 years and above (20,21) and two studies included age 15 years and above (Table 2) (22,23).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations